Neutrophil lymphocyte ratio and duration of prior anti-angiogenic therapy as biomarkers in metastatic RCC receiving immune checkpoint inhibitor therapy. Issue 1 (17th October 2017) - Jeyakumar, Ghayathri; Kim, Seongho; Bumma, Naresh; Landry, Craig; Silski, Cynthia; Suisham, Stacey; Dickow, Brenda; Heath, Elisabeth; Fontana, Joseph; Vaishampayan, Ulka
Abstract : Background: There is an unmet need to determine factors predictive of clinical benefit, to guide therapeutic sequencing and selection in metastatic RCC (mRCC). We evaluated clinical factors such as the neutrophil lymphocyte ratio (NLR) and duration of prior anti-vascular endothelial growth factor (VEGF) inhibitors, as predictors of response rate, progression free survival (PFS) and overall survival (OS) in mRCC patients treated with immune checkpoint inhibitor (ICI). Methods: Regulatory approval was obtained. A single center retrospective chart review of mRCC patients at Karmanos Cancer Institute, treated with ICI based therapy (PD-1/PD-L1 inhibitors) was conducted. Data were collected on demographics, smoking status, prognostic scoring (Memorial Sloan Kettering and Heng criteria), NLR pretherapy, post 1 and 4 doses of ICI, and duration of prior anti-VEGF therapy ≥6 months or <6. Results: 42 patients were evaluated with median age of 61 years (range, 24-85). Pretherapy NLR < 3 and ≥3 was seen in 19 (45%) and 23 (55%) patients, respectively. 24 (57%) and 18 (43%) patients had prior anti-VEGF inhibitors for a duration of ≥6 months and <6 months, respectively. 12 (29%), 22 (52%) and 8 (19%) patients had favorable, intermediate and poor risk disease based on Heng criteria, respectively. Multivariable analysis showed pretherapy NLR ≥3 was predictive of shorter PFS and OS when treated with ICI with median 3.08 months and 13.50 months, respectively, versus 15.57 months and not reached for NLR < 3 (adjusted p -values =0.003 and 0.025, respectively). Prior anti-VEGF therapy <6 months was predictive of increased likelihood of benefit from ICI therapies (adjusted p = 0.028). The median PFS was 3.72 months and 14.33 months, respectively, in cases with prior anti-VEGF therapy for ≥6 months and <6 months. Conclusion: Pretherapy NLR <3 and duration of prior anti-VEGF therapy of <6 months, are independent statistically significant predictors of longer PFS and OS with ICI therapy in mRCC. Validation is required in a larger sample size with multi-institutional collaboration.